1934
DOI: 10.1017/s0021859600007061
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on yield in cereals: VIII. Hybrid vigour in wheat

Abstract: VII. SummaryOf the genetic problems upon the solution of which immediate progress in plant breeding depends, hybrid vigour is in the front rank. This is particularly the case in naturally out-pollinating and highly self-sterile plants such as many forms of Brassica oleracea, and some of the pasture plants. But in these, genetic experiment is peculiarly difficult. With some crops, notably maize and the tomato, it has proved practicable and clearly advantageous to grow commercial crops of F1 plants. Even in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1935
1935
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…According to some authors (ENGLEDOW and PAL, 1934;cf. also DARLINGTON and MATHER, 1949), heterosis is not to be expected among self-fertilizers. Different opinions have been expressed as to the reIation between mode of fertilization and heterosis.…”
Section: A T H E Occurrence Of Heterosis In Relation T O Differentmentioning
confidence: 99%
“…According to some authors (ENGLEDOW and PAL, 1934;cf. also DARLINGTON and MATHER, 1949), heterosis is not to be expected among self-fertilizers. Different opinions have been expressed as to the reIation between mode of fertilization and heterosis.…”
Section: A T H E Occurrence Of Heterosis In Relation T O Differentmentioning
confidence: 99%
“…T. P. PALMER p. The F2 mean of p is significantly higher than the F8 mean. Engledow and Pal (1934) have reported higher germination in early generations of wheat crosses, while Copeland (1940) has reported higher growth rates of embryos in hybrid than in inbred corn. Some similar effect may account for the high p in the F2 of this cross.…”
Section: Population and Selection Studiesmentioning
confidence: 99%
“…On the basis of these, the remaining weights were corrected, as well as could be done, to give the values which would have been obtained if all the samples had been dried at 90°C. 6 Engledow and Pal (1934), working with wheat, concluded that hybrid vigor does not result solely from a greater embryo weight. These authors probably used the entire embryo as the basis for their conclusion.…”
mentioning
confidence: 99%